Athlete-Perceived Impact of Frame Running on Physical Fitness, Functional Mobility and Psychosocial Outcomes - Marietta L. van der Linden; Petra E.M. van Schie; Emma Hjalmarsson; Georgia Andreopoulou; Martine H.G. Verheul; Ferdinand Von Walden (Medical Journals Sweden, 2022)
Objective: Frame Running (RaceRunning) allows people with moderate-to-severe mobility impairments to participate in physical activity using a 3-wheeled frame with a saddle and handlebars. The aim of this study was to investigate athlete-perceived impact of Frame Running on aspects of physical fitness, functional mobility and psychosocial outcomes. Design: Survey. Participants: Frame Running athletes aged 5 years and over. Methods: A survey was distributed to athletes through their club or sports organization. Results: The survey was completed by 115 athletes (53 females). Median age was 17 years (range 5-62 years) and 64 (57%) used a wheelchair or walker for distances over 50 m. Many felt that Frame Running stretched their muscles (n = 93, 87%) and increased their self-confidence (n = 63, 93%). Four (4%) reported extreme fatigue or sore muscles after training (n = 17, 15%). Of the 110 athletes who had been participating in Frame Running for over 3 months, 46 (47%) reported being less out of breath during mobility tasks and 66 (66%) felt they had improved their functional mobility. However, 7 (7%) reported increased muscle tightness and 4 (4%) reported a Frame Running-related injury lasting more than 4 weeks. Conclusion: Frame Running is a safe physical activity with athlete-perceived benefits on physical fitness, functional mobility and psychosocial outcomes. Lay abstract Frame Running (RaceRunning) allows people with moderate-to-severe walking difficulties to walk or run independently using a 3-wheeled frame with a saddle and handlebars. In this study 115 Frame Running athletes living in the UK, Sweden or the Netherlands and aged 5 years or over (or their parents) completed a survey about taking part in Frame Running. More than half used a wheelchair or walker for distances over 50 m. Most felt that Frame Running stretched their muscles and increased their self-confidence. Four athletes perceived extreme fatigue and 17 reported sore muscles after training. Approximately half of the athletes reported that they were less out of breath during mobility tasks (walking, standing) and two thirds reported better functional mobility since they had started Frame Running. Injuries lasting more than 4 weeks were reported by 4 athletes. We conclude that Frame Running is a safe activity with the potential to improve physical fitness, functional mobility, and self-confidence.